2009
DOI: 10.1021/la901641f
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gemini Pyridinium Surfactants: Synthesis and Study of Their Surface Activity, DNA Binding, and Cytotoxicity

Abstract: New pyridinium gemini amphiphiles having ethane-1,2-dithiol spacer have been synthesized by regioselective electrophilic cobromination of alpha-olefins. Ethane-1,2-dithiol (1) and N-bromosuccinimide (6) on reaction with alpha-olefins (dodecene (2), tetradecene (3), hexadecene (4), and octadecene (5)) gave the respective 1,2-bis(2-bromoalkylthio)ethane (7-10). The bromoalkylthio ethers when reacted with pyridine (11) gave the respective gemini bispyridinium bromide (12-15). The surface properties of new geminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 57 publications
5
105
0
Order By: Relevance
“…They have been widely used in the fields of soil remediation, enhanced oil recovery, drug entrapment and release, gene therapy, etc. and are usually used in combination with nonionic surfactants [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…They have been widely used in the fields of soil remediation, enhanced oil recovery, drug entrapment and release, gene therapy, etc. and are usually used in combination with nonionic surfactants [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…49 Notice that except the MKM TM , all the other lysine derivatives studied in this work have alkyl chains of 12 carbons atoms. In the case of single chain surfactants it is expected that the toxicity increases with longer alkyl chains.…”
mentioning
confidence: 97%
“…The cationic groups commonly used are ammonium [53,54], imidazolium [55][56][57], pyridinium [58,59], lysine or arginine [60][61][62], and/or amine/polyamines [63][64][65][66][67].…”
Section: Cationic Lipids Forming Lipoplexesmentioning
confidence: 99%
“…TEM and/or cryo-TEM studies have reported many micrographs to characterize the size, shape, and morphology of a wide variety of lipoplexes as: (a) pDNA with GCLs [45,54,57,62,64,75,93,115,117,118,120], MVCLs [63], cationic polymers [107,133,[169][170][171] or polycations [40,84,100,136]; and (b) siRNA with cationic polymers [90,104]. Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation